Intelligent Lighting Control and Management System - Новоселов, С. П.; Сичова, О. В. (NURE, MC&FPGA, 2019)
This paper discusses the features of building an automated lighting control system. The architecture of the automated system is given. The block diagram is considered and its components are described. The principle of interaction of intelligent devices with the server is given. Presented the rationale and benefits from the introduction of such a system.
Keywords: light control; intelligent; led; network module; monitoring; server; IIoT